The Importance of Applying the Just-In-Time (JIT) System in Reducing Costs: An Applied Study on Public Shareholding Industrial Companies. - Sameer Suleiman Aljamal; Saed Abdulkader Thabayneh (Social Empowerment Journal, 2025)
The study aimed to identify the importance of implementing the Just-In-Time (JIT) production system in industrial companies in the Hebron area and its relationship to reducing industrial costs. The study conducted on a sample of 14 industrial companies, and data collected through a questionnaire distributed to the study sample. The data analyzed using the Correlational Descriptive Method. The results showed a positive correlation between the implementation of the JIT production system and the reduction of production costs, as well as inventory costs. However, the study revealed no significant relationship between the implementation of JIT and improvements in product quality, reduction of defective items, or reduction of labor wages. The study concluded with several recommendations, the most important of which are: expanding the scope of applying JIT principles and investing in the infrastructure that supports its implementation in order to maximize the benefits of the system.